Time Limit at vV02max and V02max Slow Component in Swimming: a pilot study of University Students - Fernandes, R.J. (2018)
The aim oftms study was to measure in swimming-pool conditions, the time to exhaustion at the minimum velocity that elicits maximal oxygen consumption (TLim-vV02max) and to verify the existence of an oxygen uptake slow component (02SC) in freestyle swimming. Ten university students performed a continuous incremental protocol for vV02max assessment. Forty-eight hours later, they swam to exhaustion at vV02max to assess TLim-vV02max and 02SC. V02 was directly measured and swimming velocity was controlled by a visual pacer. Blood lactate concentrations ([La-]) and heart rate (HR) values were also measured. Mean V02max for the incremental test was 54.2±8.2 m1.kg'l.min'l, and the correspondent vV02max was 1.19±O.08 m.S,l The mean duration ofthe TLim-vV02max test was 325±76.5 s. 02SC appeared in the allout swim at VV02max (279.0±195.2 ml.min'l) and it was found to significant1y correlate with the TLim-vV02max (r = .74, p< .05). These results demonstrated that 02SC is observed also in swimming-pool conditions and that TLim-vV02max values are in accordance with typical formulations of aerobic power training sets for swimmers.